Prevalence and burden of hepatitis D virus infection in the global population: a systematic review and meta-analysis - Chen, Hai-Yan; Shen, Dan-Ting; Ji, Dong-Ze; Han, Pei-Chun; Zhang, Wei-Ming; Ma, Jian-Feng; Chen, Wen-Sen; Goyal, Hemant; Pan, Shiyang; Xu, Hua-Guo (Gut, 2019)
ObjectiveHepatitis D virus (HDV) is a defective virus that completes its life cycle only with hepatitis B virus (HBV). The HBV with HDV super-infection has been considered as one of the most severe forms of the chronic viral hepatitis. However, there is a scarcity of data on the global burden of HDV infection.DesignWe searched PubMed, Embase, Cochrane Library and China Knowledge Resource Integrated databases from 1 January 1977 to 31 December 2016. We included studies with a minimum sample size of 50 patients. Our study analysed data from a total of 40 million individuals to estimate the prevalence of HDV by using Der-Simonian Laird random-effects model. The data were further categorised according to risk factors.ResultsFrom a total of 2717 initially identified studies, only 182 articles from 61 countries and regions met the final inclusion criteria. The overall prevalence of HDV was 0.98% (95% CI 0.61 to 1.42). In HBsAg-positive population, HDV pooled prevalence was 14.57% (95% CI 12.93 to 16.27): Seroprevalence was 10.58% (95% CI 9.14 to 12.11) in mixed population without risk factors of intravenous drug use (IVDU) and high-risk sexual behaviour (HRSB). It was 37.57% (95% CI 29.30 to 46.20) in the IVDU population and 17.01% (95% CI 10.69 to 24.34) in HRSB population.ConclusionWe found that approximately 10.58% HBsAg carriers (without IVDU and HRSB) were coinfected with HDV, which is twofold of what has been estimated before. We also noted a substantially higher HDV prevalence in the IVDU and HRSB population. Our study highlights the need for increased focus on the routine HDV screening and rigorous implementation of HBV vaccine programme.